The Social Construction of the Use of Artificial Intelligence (AI) in Learning and Character Formation - Shasliani, Shasliani; Septiantoko, Riko (JIPSINDO, 2025)
This research examines the social construction process of Artificial Intelligence (AI) usage and its contribution to character formation at SMAN 4 Makassar, responding to the duality this technology presents in education: its potential for personalized learning versus its risk to human interaction. Using a qualitative method with a phenomenological approach, this study dissects the essence of the subjective experiences of teachers, students, and stakeholders. Data were collected through in-depth interviews, participant observation, and documentation studies, with the credibility of the findings ensured through source and method triangulation. The collected data were analyzed phenomenologically and interpreted using the theoretical framework of social construction by Berger and Luckmann.The primary findings indicate that AI implementation is not merely a technical adoption but a complete social process that unfolds through three dialectical stages: externalization, where ideas are manifested through policies and infrastructure; objectivation, when AI is institutionalized into routine practices and concrete social structures; and internalization, where students accept AI as part of their subjective consciousness and academic identity. Furthermore, this research reveals the dual role of AI, not only as a learning instrument but also as an effective mediator in character formation that instills values of responsibility, integrity, and discipline. The main contribution of this study is a deep understanding of how technology integrates into the school's social system, while also highlighting that the success of this process fundamentally depends on the crucial role of teachers as facilitators who align technological potential with humanistic values.